Substrate Temperature-Dependent Structural, Optical, and Electrical Properties of Thermochromic VO2(M) Nanostructured Films Grown by a One-Step Pulsed Laser Deposition Process on Smooth Quartz Substrates - Ali Hendaoui (Advances in Condensed Matter Physics)
Thermochromic M-phase vanadium dioxide VO2(M) films with different morphologies have been grown directly on smooth fused quartz substrates using low deposition rate pulsed laser deposition without posttreatment. When the substrate temperature was increased in the range 450°C–750°C, better (011) texturization of VO2(M) films was observed along with an enhancement of their crystallinity. Morphology evolved from small-grained and densely packed VO2(M) grains at 450°C to less packed micro/nanowires at 750°C. Mechanisms behind the crystallinity/morphology evolution were discussed and correlated with the effect of the temperature on the diffusion of the adatoms as well as on the V5+ valence states content in VO2(M) films. Resistivity measurements as a function of temperature revealed that the insulator-to-metal transition features of VO2(M) films (i.e., transition temperature (TIMT), resistivity variation (ΔR), hysteresis width (ΔH), and transition sharpness (ΔT)) are strongly dependent on the processing temperature. In terms of optical properties, it was found that the open (i.e., porous) structure of the films achieved at high temperature induced an improvement of their luminous transmittance. Simultaneously, the enhancement of the films crystallinity with the temperature resulted in better IR modulation ability. The present contribution provides a one-step process to control the morphology of VO2(M) films grown on smooth quartz substrates for applications as switches, memory devices, and smart windows.